Menurunnya tingkat kesadaran hukum masyarakat di Indonesia - Puji Wulandari Kuncorowati (Universitas Negeri Yogyakarta, 2009)
In this reform era crimes occur more and more. The level of public consciousness towards law nowadays decreases. That situation impacts to the decrease the role of Government. In the ideal dimension, state apparatus should be example to increase legal consciousness among student. But in fact, thry also disobey the law. Spread of corruption proves the situation. There are to wqys then to resolve the situation. First, educational program to increase legal consciousness among society–from is urgentlY necessary. Second, legal consciousness among society needs contribution and support from State Apparatus, especiallY through their attitude toward the law.